Application of Taguchi method and grey relational analysis on a turbulated heat exchanger - Celik, Nevin; Pusat, Gongur; Turgut, Emre (Elsevier France-Editions Scientifiques Medicales Elsevier, 2018)
In this study, turbulators constructed by corrugated tapes, referred as flue breaker in the industry are used in a concentric pipe heat exchanger system. Thickness (t), width (w) and pitch (p) of these tapes and Reynolds number are addressed as the design parameters of the experimental studies. Formerly, the number of experiments namely the orthogonal array is determined via Taguchi method. Base on that array the experiments are performed and then the effects of design parameters on heat transfer and pressure loss are investigated by Analysis of Variance (ANOVA). Finally, the relationship between heat transfer and friction factor is examined by grey relational analysis. As a result, it is shown that most strength parameter on average Nusselt number is the Reynolds number. Then the width, pitch and thickness of the corrugated tapes can be ordered according to their effects' levels. However, the thickness is the most effective factor of the friction factor. Then the width and Reynolds number comes in order. The pitch has found to have negligible effect on friction factor.
Keywords: Turbulators; Corrugated tapes; Heat exchangers; Taguchi method; Design of experiment; Grey-relational analysis